Staged excision of primary periocular basal cell carcinoma: absence of residual tumour in re-excised specimens: a 10-year series. Issue 7 (4th September 2018) - McGrath, Lindsay A; Meeney, Adam; Currie, Zanna I; Mudhar, Hardeep Singh; Tan, Jennifer H
Abstract : Aims: The aim is to study staged periocular basal cell carcinoma (BCC) excision in a tertiary oculoplastic referral centre in Sheffield, UK. In particular, we examined patients with close or positive margins and no tumour seen on re-excision to identify demographics and tumour characteristics in this population. Methods: A retrospective review of medical records of 437 cases of staged periocular BCC excisions over a 10-year period (2007–2017) was carried out. Patients had surgical excision with 3 mm clinically clear margins. Staged excision was performed for all cases included in this study. Standard reconstruction techniques were employed. Histopathology was analysed for tumour type, subtype and stage. Results: Over the 10-year period, of the 437 periocular BCCs, 156 had close or involved margins. Residual tumour was found in 29 (18.6%), whereas in 122 eyelids of 120 patients (78.2%) no residual tumour was identified on histological examination. Micronodular (54.1%) and nodular (23.7%) growth patterns of BCC, as well as lower eyelid location (72.1%), were the most prevalent in this population. Two patients (1.6%) had recurrence of BCC over a mean follow-up of 57 months (range 1–125 months). Conclusions: A significant proportion of BCCs transected on initial excision show no residual tumour in the re-excision specimens. In the interval between initial excision and re-excision, there may be eradication of the residual tumour. The exact mechanisms for this are unclear, however, and re-excision remains the appropriate recommended course in the presence of involved surgical margins of periocular BCC, particularly when high-risk tumour subtypes are encountered.